RE: Comment On: Vonoprazan on the Eradication of Helicobacter pylori Infection - Huang, Jiaming; Lin, Ye (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Huang J, Lin Y. RE: Comment On: Vonoprazan on the Eradication of Helicobacter pylori Infection. Turk J Gastroenterol. 2023;34(4):436